2011
DOI: 10.7763/ijeeee.2011.v1.4
|View full text |Cite
|
Sign up to set email alerts
|

Customer Relationship Management (CRM) Processesfrom Theory to Practice: The Pre-implementation Plan ofCRM System

Abstract: Abstract-Customer relationship management (CRM) has the potential for achieving success and growth for organizations in the nowadays environment of extensive competition and rapid technological development. CRM enables organizations to know their customers better and to build sustainable relationships with them. However, CRM is considered as buzzword and it is not understood well. The main components of CRM are people, technology, and processes. This paper provides an extensive review of the literature regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 29 publications
1
19
0
3
Order By: Relevance
“…Knowledge management was found to have a direct significant impact on successful CRM systems. Past studies have obtained similar result [9], [10], [28], [29] . Thus, a positive relationship between knowledge management and successful CRM systems means that the respondents have positive satisfied towards CRM systems in the telecommunication sector in Saudi Arabia in the future.…”
Section: E Hypotheses Resultssupporting
confidence: 75%
“…Knowledge management was found to have a direct significant impact on successful CRM systems. Past studies have obtained similar result [9], [10], [28], [29] . Thus, a positive relationship between knowledge management and successful CRM systems means that the respondents have positive satisfied towards CRM systems in the telecommunication sector in Saudi Arabia in the future.…”
Section: E Hypotheses Resultssupporting
confidence: 75%
“…By organizing and using this information, organizations can design and develop better products and services (Davenport et al, 2001;Nambisan 2002). Rababah et al (2011) demonstrated that there are four major perspectives of CRM processes, which are customer facing level processes, customer oriented processes, cross-functional CRM processes, and CRM macro-level processes. Results suggest a pre-implementation plan for CRM programs/systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dalam sebuah argumen mengatakan bahwa masalah teknik bukan masalah kegagalan dalam implementasi CRM (Finnegan & Willcocks, 2007). Tetapi masalah yang meliputi perubahan dan gangguan pada organisasi, perbedaan cara pandang terhadap informasi pelanggan dan perubahan di dalam bisnis, bahkan ketidaksesuaian teknologi yang digunakan (Finnegan & Willcocks, 2006 (Fazlzadeh, Tabrizi, & Mahboobi, 2011), CRM menjadi sangat penting ketika perusahaan berubah orientasi terhadap pola pemasaran mereka, dimana CRM sendiri digunakan untuk menciptakan, meningkatkan, mempertahankan pelanggan (Rababah, Mohd, & Ibrahim, 2011). CRM dibangun di atas prinsip-prinsip hubungan pemasaran dan pelanggan yang merupakan aset bisnis, dimana implementasi CRM sendiri dapat didefinisikan sebagi sebuah struktur dan strategi bisnis, proses dan teknologi yang saling berhubungan (Erdil & Öztürk, 2016).…”
Section: Pendahuluanunclassified